2015
DOI: 10.1590/1413-81232014201.20952013
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of patients' knowledge of their medication in community pharmacies in Portugal

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 16 publications
3
26
0
3
Order By: Relevance
“…Multiple studies have demonstrated patients’ poor knowledge of their dispensed medicines [ 6 , 7 ]. A study conducted in Portugal demonstrated that eight out of 10 patients did not know anything about the medicines prescribed for them [ 8 ]. In a similar context, studies from the African continent and in particular Ghana and rural Gambia highlight the importance of patient knowledge of medicines as an antecedent to adherence to medication regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated patients’ poor knowledge of their dispensed medicines [ 6 , 7 ]. A study conducted in Portugal demonstrated that eight out of 10 patients did not know anything about the medicines prescribed for them [ 8 ]. In a similar context, studies from the African continent and in particular Ghana and rural Gambia highlight the importance of patient knowledge of medicines as an antecedent to adherence to medication regimes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has reported that medication lists produced in the ED are not accurate 10 . In this study, information from 25% of the study group on their medicines was either unavailable or limited.…”
Section: Discussionmentioning
confidence: 99%
“…The finding of use of medications during a unique situation like pediatric or geriatrics or pregnancy and breastfeeding and practice exercises or jobs is not adequate due to same previous reason. [5,7] Those results could not compare with them; most of the studies did not discuss these issues. Further studies about patients and drug-related problems in Kingdom of Saudi Arabia are highly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigated the patient's medication knowledge including drug-related problems among them. [5][6][7][8] Also, all the studies discussed a specific group of medications. There is no study discussed drug-related knowledge with patients.…”
Section: Introductionmentioning
confidence: 99%